Mathematical model to determine the index of instability in clay soils for road slopes, Huaraz – Ancash - Tarazona R., Claudia (2017)
The slopes of clayey soil and its characteristics do not allow behave in a tough way to geodynamic agents, generating instability by geological factors, similarly, the external manifestation of processes creates serious difficulties in the sustainability of transit, and physical insecurity people and vehicles by her passing, so the need to quantify these features so it can establish in the future a solution or improvement to these types of soils for roads and with the effectiveness of evaluation using mathematical models we can to determine the technical solution to propose. The mathematical model developed, used the endogenous variable displacement (I) and exogenous variables, Moisture content (W), permeability (K), density (ρ) and overload (SC), leading to the following linear regression equation.The verification technique with pre-test and post-test, was performed by involving control groups and experimental before groups and after application of the formulated linear modeling, evaluated and processed, resulting in a total displacement of the slope, 0.16 m at 3.5 months, meaning that the slope sampled presents a Slow Instability Index.